STUDI KEBUTUHAN KUANTITAS DAN KUALITAS SDM UNTUK SEKTOR-SEKTOR UNGGULAN DI KAPET SERAM-MALUKU - Elia Radianto (Journal of Indonesian Economy and Business (JIEB), 2000)
Over the last a decade, there has been increased attention to the economy of the East-Indonesia Region (KTI), arising particularly from an awareness of the existing serious ambalance in inter-regional development. In order to overcome this imbelance, the policy of developing 13 areas for an integrated economic development (KAPET) has been adopted to meet and resolve the challenges facing the East-Indonesia Region. By using a map of workers productivity and the elasticity index of employment opportunities as well as a linier trend analysis, it is possible to identify the needs for human resources in terms of quantity and quality, and to make an evaluation of the potential factors that will enhance the quality of human resources. The evaluation of the quantity and quality of human resources is based on a projection of the needs for human resources according to sectors, elasticity, and productivity. The objectives of the research are follows: 1) To identify the potentialities of the speciality sectors (i.e plantation and fishery) in Seram as an effort to enhance the capability of human resources; 2) To figure out the quantity of human resources needed for the speciality sectors in Seram; 3) To find out an appropriate set of policies that can bridge the needs for human resources in terms of quality and quantity, which are capable of attraccting private investment in Seram. The results of the study indicate that from the point of view of quantity, human resources for both the fishery an plantation sectors are adequately available for shortterm as well as long-term development. However, from the point of view of quality, the human resources in Seram have extremely low productivity. This fact shows that availability of natural resources in Seram is not complemented with the capability of human resources. Therefore, there is a need for human resources development for the purpose of exploiting the rich potentielities of the speciality sectors in Seram.